Variations in the Delivery of Primary Diabetes Care in Malaysia: Lessons to Be Learnt and Potential for Improvement - Feisul Idzwan Mustapha; Jens Aagaard-Hansen; Shiang Cheng Lim; Nazrila Hairizan Nasir; Tahir Aris; Ulla Bjerre-Christensen (SAGE Publishing, 2020)
Background: The article describes variations in the organization of clinical services for diabetes patients in 10 public primary health clinics in Malaysia with the view to learn from current innovations and improve diabetes service provision. Methods: This study combined the use of secondary data and a qualitative multicase study approach applying observations in 10 randomly selected Ministry of Health (MOH) health clinics in Kuala Lumpur and Selangor and semistructured interviews of the family medicine specialists from the same clinics. Results: Although there are specific MOH guidelines for diabetes care, some clinics had introduced innovations for diabetes care such as the novel 'personalized care', 'one-stop-centre' and utilization of patients' waiting time for health education. Analysis showed that there was room for improvement in terms of task shifting to free precious time of staff with specialized functions, streamlining appointments for various examinations, increasing continuity of consultations with same doctors, and monitoring of performance. Conclusion: We contend that there is a potential for increased effectiveness and efficiency of primary diabetes care in Malaysia without increasing the resources - a potential that may be tapped into by systematic learning from ongoing innovation.